ISCEMIC STROKE IN PREGNANT WOMEN WITH AUTOIMMUNE HEMOLYTIC ANEMIA (AIHA) AND ANTIPHOSPHOLIPID SYNDROME (APS) - Fakhrurrazy, Fakhrurazy; Khatimah, Husnul (MNJ (Malang Neurology Journal), 2025)
Background: An increased risk of thrombosis has been described in patients with autoimmune hemolytic anemia (AIHA) and antiphospholipid syndrome (APS), including stroke. The clinical manifestations of AIHA and APS occur due to thrombosis and embolism that spread to large and small blood vessels which can cause ischemia and infarction in tissues, including the blood vessels of the brain. Objective: There is a hypothesis states that free hemoglobin in AIHA and APS will cause endothelial dysfunction, inflammation, and procoagulant state that can increase the risk of stroke. This study aims to know what may caused ischemic stroke in pregnant women with autoimmune hemolytic anemia (AIHA) and antiphospholipid syndrome (APS). Methods: This is a case report of AIHA in a pregnant woman with ischemic stroke accompanied by a literature review. Conclusion: This case represents a rare arterial ischemic complication of AIHA and APS that may be associated with hypercoagulable state. Approximately 15-20% of AIHA cases are associated with arterial or venous thrombosis, and recent studies have shown an increased risk of ischemic stroke among patients with primary AIHA, especially in the first year after diagnosis.